1996
DOI: 10.1002/bies.950181006
|View full text |Cite
|
Sign up to set email alerts
|

Aging mechanisms in fruit flies

Abstract: Genetic analysis of Drosophila has provided evidence in support of two proposed evolutionary genetic mechanisms of aging: mutation accumulation and antagonistic pleiotropy. Both mechanisms result from the lack of natural selection acting on old organisms. Analyses of large numbers of files have revealed that mortality rates do not continue to rise with age as previously thought, but plateau at advanced ages. This phenomenon has implications both for models and for definitions of aging, and may be explained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 66 publications
2
62
0
2
Order By: Relevance
“…2). According to Tower (1996) adult D. melanogaster lifespan averages 40 days at 25°C. Hence, the observed longevity of the outbred flies is within the range of normal adult survival in this species under standard laboratory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…2). According to Tower (1996) adult D. melanogaster lifespan averages 40 days at 25°C. Hence, the observed longevity of the outbred flies is within the range of normal adult survival in this species under standard laboratory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A positive correlation between lifespan and antioxidant capacity has been reported in yeast, Neurospora, Caenorhabditis elegans, Drosophila melanogaster, and mammals (Fleming et al, 1992;Jazwinski, 1996;Kennedy et al, 1995;Lithgow and Kirkwood, 1996;Martin et al, 1996;Tower, 1996). Critical support for the idea that stress tolerance is related to extended life-span comes from the observation that most C. elegans longevity mutants are resistant to oxidative stress, thermal stress, and UV irradiation with the degree of tolerance often being proportional to the extention of life-span (Murakami and Johnson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, he found that at advanced ages mortality rates increase less rapidly than an exponential function, thus forestalling two centuries ago the recent fuss over &&late-life mortality deceleration'' (Fukui et al, 1993(Fukui et al, , 1996Khazaeli et al, 1996;Vaupel et al, 1998;Partridge & Mangel, 1999), &&mortality leveling o! '' (Carey & Liedo, 1995;Clark & Guadalupe, 1995;Vaupel et al, 1998), and &&late-life mortality plateaus'' (Mueller & Rose, 1996;Tower, 1996;Pletcher & Curtsinger, 1998;Wachter, 1999). For a more in-depth analysis of the previous extensive studies on mortality leveling-o!…”
Section: Introductionmentioning
confidence: 99%